Molecular epidemiology of carbapenem resistant Enterobacteriaceae in Valle d'Aosta region, Italy, shows the emergence of KPC-2 producing Klebsiella pneumoniae clonal complex 101 (ST101 and ST1789). Issue 1 (December 2015) - Del Franco, Mariateresa; Paone, Laura; Novati, Roberto; Giacomazzi, Claudio; Bagattini, Maria; Galotto, Chiara; Montanera, Pier; Triassi, Maria; Zarrilli, Raffaele
Abstract Background The spread of carbapenem resistantEnterobacteriaceae (CRE) is an emerging clinical problem, of great relevance in Europe and worldwide. The aim of this study was the molecular epidemiology of CRE isolates in Valle d'Aosta region, Italy, and the mechanism of carbapenem resistance. Results Sixty consecutive CRE samples were isolated from 52 hospital inpatients and/or outpatients from November 2013 to August 2014. Genotyping of microbial isolates was done by pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST), carbapenemases were identified by PCR and sequencing. Carbapenem resistance gene transfer was performed by filter mating, plasmids from parental and transconjugant strains were assigned to incompatibility groups by PCR-based replicon typing. Molecular characterization of CRE isolates assigned 25Klebsiella pneumoniae isolates to PFGE types A1-A5 and sequencing type (ST) 101, 17 K. pneumoniae isolates to PFGE type A and ST1789 (a single locus variant of ST101), 7 K. pneumoniae isolates to PFGE types B or C and ST512, 2 K. pneumoniae isolates to PFGE type D and ST405, and 5Escherichia coli isolates to PFGE type a and ST131. AllK. pneumoniae ST101 and ST1789 isolates were extended-spectrum beta-lactamase (ESBL) producers and carriedbla CTX-M-1 group gene; 4 K. pneumoniae ST101 isolates were resistant to colistin. Molecular analysis of beta-lactamase genes identifiedbla KPC-2 andbla CTX-M-group 1 into conjugative plasmid/s assigned to IncFII incompatibility group in ST101 and ST1789K. pneumoniae isolates, bla KPC-3 into conjugative plasmid/s assigned to IncF incompatibility group in ST512 and ST405K. pneumoniae isolates, bla VIM-1 into conjugative plasmid/s assigned to IncN incompatibility group in ST131E. coli isolates. Conclusions The spread of CRE in Valle d'Aosta region was caused by the selection of KPC-2 producingK. pneumoniae ST101 and ST1789 epidemic clones belonging to clonal complex 101, KPC-3 producingK. pneumoniae epidemic clones assigned to ST512 and ST405, and VIM-1 producingE.coli ST131 epidemic clone. Carbapenem resistance, along withbla KPC-2, bla KPC-3 andbla VIM-1 carbapenemase genes, was transferred by conjugative plasmids assigned to IncFII, IncF, and IncN incompatibility groups, respectively, in filter mating experiments. The emergence of colistin resistance was observed in KPC-2 producingK. pneumoniae ST101 isolates.